Managing The Tools Of Fiscal Policy Towards Achieving Fiscal Discipline In Iraq: An Analytical Study Of Financial Policy Indicators in Iraq For The Period (2004-2018) - Mohammed, ThaerSaadoon (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to study the financial policy indicators in Iraq for the period (2004-2018), which is the period that witnessed low growth in the real sector that made the country live on oil revenues, as the research tried to answer the following question: What is the extent of adopting an effective and appropriate financial policy for the level of activity and economic growth in Iraq? The research started on the premise that the implementation of a fiscal policy with a high degree of fiscal discipline is capable of moving towards achieving economic growth. To take note of the above, the research was divided into three parts. The first part dealt with the theoretical framework for the concept of fiscal policy and fiscal discipline, while the second part dealt with analyzing the indicators of managing financial policy, and the third part was devoted to conclusions and recommendations. As the research reached an increase in the degree of fiscal policy response to oil revenues due to the Iraqi economy’s dependence on a single government resource, which is oil revenues, and that any shock in these prices will negatively affect development opportunities in Iraq. The recommendation was made to shift from the rentier nature by supporting the private sector and projects. Productivity in the agricultural, industrial, and service sectors.